Enzymes Involved in Lignin Biosynthesis as Resistance to Wilt Disease (Fusarium solani F. Sp. dalbergiae) in Shisham - ., Dayaram; Sharma, S.; Kumar, M.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Nine different girth regimes of healthy and diseased shisham trees (Fusarium solani f. sp. dalbergiae infected) were used to study the biochemical basis of resistance of younger trees than that of older trees. Level of activities of phenylalanine ammonia-lyase, peroxidase, catalase and lignin contents were significantly higher in healthy shisham trees than those in diseased or wilted shisham trees of the same age group. The relatively high activation of enzymes phenylalanine ammonia-lyase, peroxidase and catalase at younger stages of the trees induced higher lignin synthesis which led them to relatively high resistant to wilt disease.